2021
DOI: 10.1002/tpg2.20165
|View full text |Cite
|
Sign up to set email alerts
|

Selection signatures in the CIMMYT International Elite Spring and Semi‐arid Wheat Yield Trials

Abstract: The International Maize and Wheat Improvement Center (CIMMYT) annually distributes advanced wheat (Triticum aestivum L.) breeding lines to collaborators worldwide through the International Wheat Improvement Network. Lines are disseminated through international nurseries, including the Elite Spring Wheat Yield Trial (ESWYT) targeted to optimal (irrigated and high production) wheat production areas and the Semi‐arid Wheat Yield Trial (SAWYT) targeted to low rainfall environments. A total of 2,184 wheat lines tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Many previous studies in wheat have shown selection signatures for Vrn-1 loci 14,23,70,71 . In our study and an earlier study 72 , signatures of selection were not observed for Vrn-1.…”
Section: Discussionmentioning
confidence: 96%
“…Many previous studies in wheat have shown selection signatures for Vrn-1 loci 14,23,70,71 . In our study and an earlier study 72 , signatures of selection were not observed for Vrn-1.…”
Section: Discussionmentioning
confidence: 96%
“…This introgression carries several important disease-resistance genes (e.g., Lr37 and Sr38-Yr17-Lr34 ) to various important rust diseases [ 39 , 40 ]. In addition, the introgression also appears to improve yield stability [ 41 ] and resistance to rice blast [ 42 ], all traits that are of great importance for many wheat breeding programs worldwide. For a large proportion of our wheat cultivars, molecular marker information for the disease resistance cluster Sr38-Yr17-Lr34 ( Table S3 ) is available, which matches almost perfectly with the different QTL alleles of prot288.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high marker densities available in wheat, haplotypes-based GWAS studies and epistatic interaction analyses have become possible in wheat, providing high-resolution dissection of complex traits [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Additionally, a range of new genetics and genomics analyses are now possible, including genomic selection (GS) and selective sweep analyses, which require genome-wide high-density markers [ 85 , 86 , 87 , 88 ]. The integration of genomics in wheat improvement programs has restructured breeding programs globally, from conventional to genomics-assisted ones, promoting marker-assisted selection (MAS) and GS for achieving faster and more reliable breeding outcomes [ 89 ].…”
Section: Genomic Approachesmentioning
confidence: 99%